Pengaruh Penilaian Kinerja Pegawai terhadap Promosi Jabatan pada Pengadilan Agama Jakarta Timur - Sulandari, Nisa; Rosento, Rosento; Marthanti, Amas Sari (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
Abstract- Pengadilan Agama East Jakarta doing performance appraisal employee who works to find out the deficiencies of the officers in carrying out the task given, employee performance appraisal program serves to provide an opportunity for employees in works like getting a promotion Office. Researchers using the sample as much as 73 respondents with sampling techniques, namely the determination of saturated samples when all members of the population made a sample, this is done when the population was relatively small and the collection of data using methods of dissemination questionnaires and were tested with the method of data analysis. Based on the results of research on the Religious Court in East Jakarta the author concludes that the existence of a strong relationship, which can be seen from the results of the test of the correlation coefficient of calculation results and koefesien 0.663 determination showed 0.440 the influence of employee performance assessment against the Promotion Office of 44.0% and the rest of 56.0% are influenced by other factors as well as the results of statistical tests (regression Results calculate r is Y = 13.319 + 0, 714X show if performance assessment or X = 0, then the Promotion Office of 13.319 and if X goes up 1 point then the increase in performance assessment occurs 1% then it will raise the Promotion Office of 0.714%.Keywords: The Assessment , Promotion Office